Quality of Philippine dried salted herring (Sardinella Fimbriata) - Alano, Alexie Servan; Gabriel, Alonzo (2005)
ABSTRACT This study dealt with the quality assessment of salted herring during the 2 mechanical drying processes. Phase 1 of the study involved the establishment of a generic dried salted herring (DSH) process flow based on the protocols of two DSH processors from Ligtong, Cavite and Dalahican, Quezon. The second phase dealt with the assessment of the changes in physico-chemical, microbial and sensory quality of salted herring dried using a cabinet and a high performance mechanical dryer. Microbiological evaluations showed a decreasing microbial count as the drying process progressed. Quality assessment of sun- and mechanically-dried salted herrings were also conducted. Mechanically dried salted herrings had the best microbial quality. Sensory testing showed samples from Dalahican Quezon as most acceptable in terms of general acceptability and other quality characteristics. The thermal inactivation of Pseudomonas aeruginosa 1244 during salted herring drying was established and resulted to D-values of 0.794, 0.84 and 0.404 at 60, 75 and 90° exposure temperatures, respectively.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Dried fish -- Philippines; Fishes -- Philippines; Herring